A proposal for the development of the PNOC library into an information center a five-year program - Martin, Carmelita M.
The Philippine National Oil Company is one of the country's largest and most important corporations. It plays a major role in the development of the Philippine economy because it is tasked with the maintenance of a reliable supply of energy for the country. To help the Company in pursuing its mandated objectives, it is important that its requirements for information services be adequately met. Unfortunately, the present Library does not have the capabilities to provide the needed information services. It is for this reason that this study of a plan for the transformation of the PNOC Library into an Information Center has been made.